Moral vulnerability: a view of exclusions in the context of bioethics - Sanches, Mário Antônio (2018)
This article proposes the discussion of human vulnerability, pointing out that the discussion of social and existential vulnerability is not enough to understand certain situations of discrimination and exclusion to which some people are submitted. It is a theoretical review of the studied subject, with an interdisciplinary approach, as it is used in bioethics. The literature on bioethics already shows the distinction between being vulnerable, an element of human condition and living a situation of specific vulnerability. Being involved in a vulnerable situation indicates the so called ‘social vulnerability’. However, there are situations where the condition of vulnerability of some people is explicitly built from moral, cultural and theoretical elements, that are explicitly espoused and defended. The article approaches the concept of ‘moral vulnerability’ within the framework of bioethics, as a key to understand exclusion and discrimination to which some groups are presently submitted, especially black people, women and homosexuals.